Metonymy in language and thought - Panther, Klaus-Uwe, 1942-; Radden, Günter (Human cognitive processing, 1999)
Metonymy in Language and Thought gives a state-of-the-art account of metonymic research. The contributions have different disciplinary and theoretical backgrounds in linguistics, psycholinguistics, psychology and literary studies. However, they share the assumption that metonymy is a cognitive phenomenon, a "figure of thought," underlying much of our ordinary conceptualization that may be even more fundamental than metaphor. The use of metonymy in language is a reflection of this conceptual status. The framework within which metonymy is understood in this volume is that of scenes, frame